Hennie van Vuuren, Apartheid Guns and Money: A Tale of Profit (Historia, 2021)
Hennie van Vuuren’s book, Apartheid Guns and Money: A Tale of Profit, is an astonishing 514-page masterclass in the wheeling and dealing of apartheid South Africa’s arms programme. It sets out to demonstrate how “networks of deep state actors operate in subverting the rule of law” (p 503). In an era of democratic South African politics where the games of political spin, blame, secrets and lies run rampant, this book is a telling reminder that history influences and creates the present. The multibillion-dollar arms deal in the late 1990s has shaped South Africa’s political landscape over the past 20 years, but as Van Vuuren contends, “the arms deal did not happen in a vacuum”. The past matters.
Keywords: Apartheid; South African politics; Hennie van Vuuren’; Thabo Mbeki